2006
DOI: 10.1159/000095388
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling the Origins of Africa, India and Madagascar with Vertebrate Dispersal Scenarios

Abstract: Africa, India and Madagascar were once part of the supercontinent of Gondwana. This land mass began to fragment approx. 170 million years ago, and by 83 million years, all of the major components we recognize today were separated by tracts of water. Madagascar’s fossil record and estimates of the timing of the extant vertebrate radiations in Madagascar are not easily reconciled with this history of fragmentation. Fossil faunas that lived prior to approx. 65 million years had a cosmopolitan flavour, but this wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 84 publications
1
47
0
2
Order By: Relevance
“…Yoder and Nowak, and Masters and colleagues (Yoder and Nowak 2006;Masters, de Wit, and Asher 2006) offer detailed, but rather different, reviews of the complex geological history of Madagascar and its interaction with the rest of Gondwana (see also Leigh et al 2007). Yoder and Nowak highlight recent phylogenetic evidence of numerous taxa and how results generally are at odds with predictions based on Gondwanan vicariance, rather pointing towards transoceanic dispersal during the Cenozoic as the primary biogeographical force.…”
Section: Madagascarmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoder and Nowak, and Masters and colleagues (Yoder and Nowak 2006;Masters, de Wit, and Asher 2006) offer detailed, but rather different, reviews of the complex geological history of Madagascar and its interaction with the rest of Gondwana (see also Leigh et al 2007). Yoder and Nowak highlight recent phylogenetic evidence of numerous taxa and how results generally are at odds with predictions based on Gondwanan vicariance, rather pointing towards transoceanic dispersal during the Cenozoic as the primary biogeographical force.…”
Section: Madagascarmentioning
confidence: 99%
“…After the separation of Madagascar with Africa and India, oceanic currents are thought to have been favourable to dispersal on rafts from Africa to Madagascar, however, in the present day, currents go in the opposite direction, and are more favourable for colonization from Madagascar to Africa. How long the present day currents have persisted is debated, and some have suggested they may have prevailed for as much as 50 Ma (Masters, de Wit, and Asher 2006 and references therein), thus drastically reducing opportunities for colonization of Madagascar from Africa. However, an exciting new paleooceanographic modelling study concluded that strong oceanic currents did flow from eastern Africa to Madagascar during the Palaeogene, with occasional currents strong enough to cross the Mozambique channel in less than a month (Ali and Huber 2010).…”
mentioning
confidence: 99%
“…15 One proposal regarding the origin of these mammals on Madagascar suggests the brief existence of a land-bridge, along the Davie Ridge fault line, during this period. 15,16 The less mobile the species, the more likely its divergence into two species resulted from continental separation. To minimise the effect of dispersal between continents, taxa were selected for their reduced ability to have undergone dispersal-driven speciation.…”
mentioning
confidence: 99%
“…Secondly, fossils with European (Laurasian) kinship and representing the precursors of modern perissodactyls, primates and rodents were found in north-western India mixed with typical Gondwanan fauna, from a period (54 Mya) that predated the collision of India with Asia (Rose et al, 2014). This has given rise to suggestions of occasional Laurasian land connections (chains of island stepping-stones) to India as the island plate traversed the ocean towards northern Asia (Masters et al, 2006;Ali et al, 2008), particularly during ocean low levels in the Oligocene (Schlanger and Silva, 1986;Miller et al, 2008).…”
Section: The "Out Of India" Hypothesismentioning
confidence: 99%